The manifestations of interculturality in the verbal interactions of Algerians on the social network Facebook - Aicha Lilia, Chennouf (Journal of Social Sciences and Humanities, 2021)
Algeria knows a particular linguistic and cultural situation, due to repeated invasions. It is a crossroads where several languages and cultural diversity meet. We cannot speak of languages and cultures without evoking the interest of interculturality, which allows any individual to be efficient, comfortable and happy in all situations of intercultural communication and to accept the other with its differences. Linguistic mixing has fostered the existence of a linguistic diversity that arises in the language practices of Algerian speakers. In his daily exchanges, the Algerian speaker alternates between French and dialectal Arabic in the same utterance, this is a common phenomenon in situations of language contact and that sociolinguists call codec alternation. Code alternation has become a frequent strategy for the Algerian speaker, which has prompted us to ask ourselves whether the use of the French language could carry a cultural dimension. Since any language conveys its own culture, we assume that the Algerian speaker, in contact with the French language, in addition to linguistic competence, he acquires cultural and intercultural competence. To give a practical aspect to our research, our choice fell on Facebook. We will try to focus on the manifestations of interculturality in the interactions of users of this social network.